HUBUNGAN ANTARA PRODUKTIVITAS PEKERJA GALANGAN DAN TEKNIK KERJA TERHADAP KINERJA GRAVING DOCK (STUDI KASUS DI PT. JANATA MARINA INDAH SEMARANG) - Suharto Suharto (Center for Research and Community Service (LPPM) University of Abulyatama, 2015)
Shipyard industry is one of the most important chain on the national shipping system. Notably to maintains the vessels condition in order to get adjustment of The Indonesia Classification Bureaustandard. Shipyard’s productivity depends on the graving dock capacity, man productivity and work method. Empirical studies show that man competiveness and productivity and effective work method are primary factors which affects choice rate from shipping companies to a shipyard. The research goal was to analyzed the effect of man productivity and work method toward graving dock performance in PT. Janata Marina Indah Semarang. Multiple linear regression used as a method in this research. Methodology use basic is difficulty to identify relating directly from man productivity and work method toward graving dock performance. The sampling method using purposive random sampling with 35 respondents who have long experience in the graving dock works. The result of regression analysis is: Y= -0,357 + 0,256 X1 + 0,249 X2. The result shows that two factors both man productivity and work method, are have significant effect toward graving dock performance.